Evaluación de la pertinencia de la carrera de Ingeniería Ambiental en la ESPAM MFL y las necesidades de su entorno - Mieles Ponce, Vicente Ezequiel (2016)
Seeks to assess the relevance of environmental engineering in the ESPAM MFL and the needs of your environment. Research was to evaluate the relationship between the relevance of career environment of the ESPAM MFL the needs of national, regional, provincial and local environments associated with the requirements of technological and scientific development, based on the corresponding plans. Thus the environmental engineering degree will contribute to the achievement of major aspects of Regional Planning (zone 4: Manabi, Santo Domingo de los Tsáchilas), according to shafts Natural Areas and protected (Parque Nacional Machalilla (PNM) Reserva ecológica Mache Chindul (REMACH) and coastal Pacoche, forest guard of Tanti marine wildlife refuge); as well as the economic system production of cattle, milk, pig production, fishing, and aquaculture. Engineers and engineers environmental of the agricultural Polytechnic School of Manabi - MFL, accordingly with the missions and visions, both institutional as's own career, have the necessary capabilities and enough to conceive, analyze, plan, design, implement, pollutants, both solid and liquid and gaseous materials processing systems, sustainable management of river basins, for the environmental management of production and services entities in the same frame as well as the proposal of local and regional environmental management processes, promoting the minimization of environmental impact and, therefore, increase the quality of life of the population, observing the principle of intergenerational responsibility.